2018
DOI: 10.1007/s13197-018-3115-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antibacterial protein from Lactobacillus spp. and preparation of probiotic curd

Abstract: The study was aimed to isolate antagonistic lactobacilli and the molecules responsible for their antagonistic ability from curd. Preparation of probiotic curd and the ability of the selected lactobacilli to suppress the pathogen therein was also assessed. All the 116 isolates were identified as spp. based on morphological, biochemical and curdling assays. Five of these lactobacilli (Lb-17, Lb-33, Lb-108, Lb-112, and Lb-N3) were found most promising to inhibit all test pathogens (, ,, and). The cell-free cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…LAB, not only as antagonists of pathogenic microorganisms but also producers of antimicrobial metabolites, have attracted much attention. Several studies have proven that LAB can inhibit the growth of pathogenic microorganisms via multiple mechanisms, including competitively inhibiting pathogen binding, enhancing the host immune system, and producing pathogen growth-inhibitory compounds such as organic acids, bacteriocins, and hydrogen peroxide [9]. erefore, LAB could be candidate biological preservatives in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…LAB, not only as antagonists of pathogenic microorganisms but also producers of antimicrobial metabolites, have attracted much attention. Several studies have proven that LAB can inhibit the growth of pathogenic microorganisms via multiple mechanisms, including competitively inhibiting pathogen binding, enhancing the host immune system, and producing pathogen growth-inhibitory compounds such as organic acids, bacteriocins, and hydrogen peroxide [9]. erefore, LAB could be candidate biological preservatives in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Basit et al (2020) reported the antimicrobial effect of phytobiotics or phytogenic feed additives on various pathogenic bacteria, including S. aureus , isolated from the caecal microbiota of broiler chickens. Probiotics have been reported to produce antimicrobial proteins called bacteriocins that suppress the growth of other bacteria (Benítez‐Chao et al, 2021; Negi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Negi et al found that the antimicrobial activity of cell-free supernatants of Lactobacillus spp. was dependent on the presence of an antimicrobial protein (21). Mazoteras et al (22) reported that biofilm on IOLs can be found many years after uncomplicated cataract surgeries.…”
Section: Discussionmentioning
confidence: 99%